Mini Research Learning on Ecosystem Material Based Semarang Local Potential Towards Critical Thinking and Environmental Awareness Among Elementary School Student - Izza, Fika Rofiuddin; Saptono, Sigit; Irsadi, Andin (Universitas Negeri Semarang, 2025)
This study aims to analyze the Critical Thinking and Environmental Awareness Among Elementary School Student through mini research learning on Ecosystem material, utilizing Semarang’s local potential. The research method employed is qualitative with descriptive qualitative analysis. The subjects of the study were Phase C students from Grade 6 at elementary school (SD) Nongkosawit 01 and SD Islam Bintang Juara, located in Gunungpati, Semarang City. Mini research learning is a teaching method that guides students in conducting scientific processes. This approach leverages Semarang’s local potential, specifically the Tapak Mangrove Forest in Tugurejo, Semarang City, allowing students to learn about the Ecosystem material more contextually and concretely. Ecosystem material is one of the essential topics in the curriculum. The study assessed two main student character traits: critical reasoning and environmental awareness. The analysis of critical reasoning, based on the LKPD assessment and N-gain scores, showed good results. Similarly, environmental awareness, as measured by a questionnaire, indicated that 79.64% of students demonstrated strong character in this area. Based on the findings, mini research learning that incorporates Semarang’s local potential is effective in fostering critical reasoning and environmental awareness among elementary school students.